APPLICATION METHOD FOR PREDICTION SIMPLE LINEAR STATIONARY SALES OFFICES IN XYZ COMPANY PASCAL PROGRAMMING LANGUAGE - Rudi Supangkat; Cut Asiana Gemawaty, Skom, MMSI (Jurnal Sistem Informasi, 2005)
In this scientific writing, writing to discuss developments in the field of analysis thatis closely related to the development of prediction methods (forecasting). Here theauthor uses simple linear regression method with the determinism of time that wasapplied to the Pascal programming language, where the application is used to predictsales of stationery at XYZ company in the next few years.Pascal programming language is a high level language (high level language) whoseorientation on all objectives, was designed by Professor Niklaus Wirth from theTechnical University in Zurich, Switzerland.By using simple linear regression method of application is expected to help thecompany to take decisions and make better planning and precise, particularly in theareas of sales for the next few years.